2020
DOI: 10.14740/wjon1275
|View full text |Cite
|
Sign up to set email alerts
|

Gustave Roussy Immune Score and Royal Marsden Hospital Prognostic Score Are Prognostic Markers for Extensive Disease of Small Cell Lung Cancer

Abstract: Background: The Royal Marsden Hospital prognostic score (RMH score) and the Gustave Roussy immune score (GRIm-score) were developed in order to select more suitable patient for phase I trials. Lactate dehydrogenase (LDH) and serum albumin concentration are common risk factors to these two systems. As the third risk factor, the RMH score and the GRIm-score adopt number of metastatic sites and neutrophil-to-lymphocyte ratio (NLR), respectively. We aimed to investigate whether these two systems are also useful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This study retrospectively collected 128 patients ( Supplementary Material 1 , www.wjon.org ). This cohort was the same as that of our previous study [ 12 ]. The inclusion criteria were as follows: 1) Cytologically or histologically SCLC; 2) The first-line, cisplatin (CDDP) or carboplatin (CBDCA)-containing chemotherapy which had been initiated between September 2007 and March 2018 at Osaka Police Hospital; 3) Clinical stage IIIB or IV in the seventh lung cancer tumor-node-metastasis (TNM) classification and staging system published by the International Union Against Cancer (UICC) [ 13 ]; 4) Abdominal plain or enhanced computed tomography (CT) scan covering L3 level within 3 months, serum albumin concentration (mg/dL) and lactate dehydrogenase (LDH) (IU/L) in peripheral venous blood sampling within 2 weeks before the initiation of the first-line chemotherapy; and 5) No indication for curative-intent thoracic radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…This study retrospectively collected 128 patients ( Supplementary Material 1 , www.wjon.org ). This cohort was the same as that of our previous study [ 12 ]. The inclusion criteria were as follows: 1) Cytologically or histologically SCLC; 2) The first-line, cisplatin (CDDP) or carboplatin (CBDCA)-containing chemotherapy which had been initiated between September 2007 and March 2018 at Osaka Police Hospital; 3) Clinical stage IIIB or IV in the seventh lung cancer tumor-node-metastasis (TNM) classification and staging system published by the International Union Against Cancer (UICC) [ 13 ]; 4) Abdominal plain or enhanced computed tomography (CT) scan covering L3 level within 3 months, serum albumin concentration (mg/dL) and lactate dehydrogenase (LDH) (IU/L) in peripheral venous blood sampling within 2 weeks before the initiation of the first-line chemotherapy; and 5) No indication for curative-intent thoracic radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with it is the Seigo Minami. [ 16 ] Studies in small cell lung cancer have found that OS was significantly shorter in high GRIm-score group than in low group (median 6.1 vs 11.4 months, P < .01). They also confirmed the high GRIm-score (HR 1.80, 95% CI 1.20–2.72, P < .01), as separate and prognostic factors of OS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] The GRIm score is widely used in clinical immunotherapy or non-immunotherapy for various solid tumors, such as small cell lung cancer. [ 16 ] non-small cell lung cancer [ 12 , 17 ] and esophageal cancer, [ 18 ] and its role of prognosis evaluation has been confirmed. Studies show that a high GRIm score before treatment predicts worse overall survival (OS) and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients with a low RMH score (0-1) had a significantly longer median overall survival (OS) of 33 weeks compared to 15.7 weeks for patients with a high RMH score (2)(3). After that, the prognostic value of the RMH score for predicting outcomes was explored for various cancers on phase 1 trial cohorts, as well as a few cohorts from real-world settings [8,9]. However, this raises questions about the RMH score's generalizability in clinical trials to the larger and more variable patient populations encountered in daily clinical practice, necessitating a review of the available evidence.…”
Section: Introductionmentioning
confidence: 99%